Species, cultivar and seeding rate effects on non‐irrigated, pesticide‐free athletic fields playing surface quality. Issue 1 (8th March 2021) - Maxey, Garrett L.; Wallace, Victoria H.; Guillard, Karl; Henderson, Jason J.
Abstract: Maintaining high‐quality athletic field playing surfaces without the use of synthetic pesticides is challenging. Little research is available regarding the best overseeding strategies for non‐irrigated, pesticide‐free, cool‐season athletic fields. The objectives of this study were to determine the effects of turfgrass species, cultivar, seeding rate, and seasons on turfgrass color, dark green color index (DGCI), cover, weeds, overall quality, surface hardness and volumetric water content when overseeded under trafficked conditions. Experiments were set out as randomized complete block designs arranged in a 3 × 2 × 2 factorial with three replications. Treatments consisted of three turfgrass species, perennial ryegrass ( Lolium perenne L.) (PRG), tall fescue [ Schedonorus arundinaceus (Schreb.) Dumont] (TF), and Kentucky bluegrass ( Poa pratensis L.) (KBG), two overseeding rates, low and high, and two cultivar types, inclusion or exclusion of cultivars on the Turfgrass Water Conservation Alliance (TWCA) list. Mean responses across three locations and three years indicated that species selection has the most influence on successful overseeding with little differences detected between rate of overseeding or cultivar selection. Perennial ryegrass, regardless of seeding rate, had significantly higher color, quality, percent turfgrass cover, desirable species index, and least percent weed cover compared with TF or KBG. Based on the results of this study, the most effective overseeding strategy for improving playing surface conditions on heavily trafficked, non‐irrigated, pesticide‐free, cool‐season athletic fields is overseeding with PRG.